Academics' perceptions of continuous and collaborative curriculum review: An Australian case study. (September 2015) - Bird, Jennifer; van de Mortel, Thea; Holt, Julienne; Walo, Maree
Abstract: Tourism and hospitality educators face particular challenges in meeting current national and international pressures and requirements for accreditation of their curricula within national standards frameworks. Conventional curriculum design and review processes may not suffice in meeting these challenges. In other disciplines and subject areas innovative models of continuous and collaborative curriculum design processes are responding to these challenges, yet the literature on this topic is absent in tourism and hospitality education. This case study investigates academics' experiences and perceptions of a continuous and collaborative curriculum review process introduced in a School of Tourism and Hospitality Management (STHM) at an Australian regional university. The study found that academics valued the opportunities the process afforded to improve the curriculum from a whole-of-program perspective. The collaborative nature of the process, the opportunities for scholarship of teaching outcomes and the building of multidisciplinary relationships were also seen as positive outcomes. Concerns included a lack of clarity regarding procedures for acting upon matters identified during review and challenges associated with collaboration across multiple campuses.